2017
DOI: 10.1213/ane.0000000000001798
|View full text |Cite
|
Sign up to set email alerts
|

Dural Puncture Epidural Technique Improves Labor Analgesia Quality With Fewer Side Effects Compared With Epidural and Combined Spinal Epidural Techniques: A Randomized Clinical Trial

Abstract: Analgesia onset was most rapid with CSE with no difference between DPE and EPL techniques. The DPE technique has improved block quality over the EPL technique with fewer maternal and fetal side effects than the CSE technique for parturients requesting early labor analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(99 citation statements)
references
References 31 publications
3
89
0
7
Order By: Relevance
“…This corroborates the results in this study that DXMS pretreatment is effective in reducing the incidence of postoperative lower back pain in epidural labor analgesia. In the study of Chau et al ( 16 ) and Wilson et al ( 17 ), it was shown that the number of punctures is a direct factor affecting postoperative lower back pain. Therefore, the effect of DXMS on patients with different times of punctures was investigated and it was found that either with one puncture or many times of puncture, the incidence of postoperative lower back pain in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates the results in this study that DXMS pretreatment is effective in reducing the incidence of postoperative lower back pain in epidural labor analgesia. In the study of Chau et al ( 16 ) and Wilson et al ( 17 ), it was shown that the number of punctures is a direct factor affecting postoperative lower back pain. Therefore, the effect of DXMS on patients with different times of punctures was investigated and it was found that either with one puncture or many times of puncture, the incidence of postoperative lower back pain in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Then, an epidural catheter was placed by needle through needle technique. The DPE technique is a modi cation of the CSEA technique, where a dural perforation is created with a spinal needle, but intrathecal medication is withheld [12]. For induction of EPI and DPE, levobupivacaine (0.125%) with fentanyl (5 μg/mL) was administered incrementally (10-20 ml).…”
Section: Standard Protocol For Labor Epidural Analgesiamentioning
confidence: 99%
“…DPE technique may thus provide a faster onset of labour analgesia giving a better quality, reliable, and consistent block compared with the epidural technique with less maternal and foetal side effects compared with the CSE technique. [ 24 25 ]…”
Section: Dural Puncture Epidural Techniquementioning
confidence: 99%